2021
DOI: 10.1186/s12884-021-03836-z
|View full text |Cite
|
Sign up to set email alerts
|

Lower birth weight-for-age and length-for-age z-scores in infants with in-utero HIV and ART exposure: a prospective study in Cape Town, South Africa

Abstract: Background Successful scale-up of antiretroviral therapy (ART) during pregnancy has minimized infant HIV acquisition, and over 1 million infants are born HIV-exposed but uninfected (HEU), with an increasing proportion also exposed in utero to maternal ART. While benefits of ART in pregnancy outweigh risks, some studies have reported associations between in utero ART exposure and impaired fetal growth, highlighting the need to identify the safest ART regimens for use in pregnancy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
4
15
0
Order By: Relevance
“…4 A). Our finding of lower WAZ at birth among HEU infants is consistent with several other studies conducted in African populations [ 27 , 30 , 58 – 60 ]. When our HEU infants were grouped by breastfeeding status, the breastfeeding HEU infants had significantly higher WAZ at 6 weeks postpartum compared to non-breastfeeding HEU infants (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…4 A). Our finding of lower WAZ at birth among HEU infants is consistent with several other studies conducted in African populations [ 27 , 30 , 58 – 60 ]. When our HEU infants were grouped by breastfeeding status, the breastfeeding HEU infants had significantly higher WAZ at 6 weeks postpartum compared to non-breastfeeding HEU infants (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that HEU infants have lower WAZ compared to HUU infants [ 27 30 ]. Our results are also consistent with those findings (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, residual confounding cannot be excluded. For example, we could not assess the effect of maternal viral loads and CD4 cell counts due to limited reporting and lack of adjustment for these confounders in most of the studies include d. 17,21,[30][31][32]34,37,43,44,[46][47][48][49][50][51][52][53][54] Still, for some of the outcomes studied, such as PTB, the risk was significantly elevated in the majority of the studies with narrow CIs. Third, some of the measured outcomes, such as preeclampsia, 17,21,31,33,36,37,39 were reported by only a few studies (seven).…”
Section: Discussionmentioning
confidence: 99%
“…All covariates in univariable analyses with a p -value of 0.10 were included in multivariable analyses. Additionally, an a priori decision was made to include maternal age in the multivariable model, regardless of univariable p-value [ 3 , 32 , 33 ]. Infant feeding practice was defined as exclusive breastfeeding, formula feeding, or mixed feeding based on maternal report.…”
Section: Methodsmentioning
confidence: 99%